MiR-15a-5p Knockdown up-Regulated ABCB1 Expression and Abated HNSCC Progression via the NF-κB Signaling Pathway - Jing Liu; Chaoyang Lv; Sis Aghayants; Yingying Wang (Journal of Investigative Surgery)
Background The high invasion and heterogeneity of head and neck squamous cell carcinoma (HNSCC) commonly leads to poor clinical outcomes. Identification of reliable biomarkers for HNSCC is imperative.Methods The targeted gene with the highest mutation was screened out in cBioPortal database, and the interactive microRNAs (miRNAs) were identified by miRNA-mRNA co-expression analysis. CCK-8 and transwell assays were used to explore the proliferative, migrative, and invasive behaviors of HNSCC cells. The dual-luciferase reporter assay and cell transfection experiment were conducted. The role of miR-15a-5p was investigated in the in vivo xenograft mouse model.Results ATP binding cassette transporter 1 (ABCB1) had the highest mutation frequency and multiple mutation types in HNSCC, and the decreased ABCB1 was significantly related to better prognosis of HNSCC patients. MiR-15a-5p was a regulator for ABCB1, which was up-regulated after miR-15a-5p inhibition in vitro. Furthermore, the miR-15a-5p knockdown significantly suppressed HNSCC cell proliferation, migration, and invasion in vitro, and reduced the HNSCC tumor growth and migration capabilities in vivo, possibly through NF-κB signaling pathway.Conclusion Collectively, miR-15a-5p knockdown increased the ABCB1 level and abated the HNSCC progression via the NF-κB signaling pathway. ABCB1 and miR-15a-5p were underlying predictors for HNSCC therapeutic biomarkers.